ASSESSMENT OF THE PHYSICAL CONDITION AND STANDARD OF LIVING OF ELDERLY PEOPLE - Evseeva O.E.; Ladygina E.B. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to assess the physical functioning and quality of life of senior citizens based on the monitoring results. Methods and structure of the study. Testing was conducted in accordance with the technical specifications of the research work on the stated topic and included: analysis of regulatory documents on the problem of active longevity; monitoring the level of physical functioning and quality of life of senior citizens aged 60 to 78 years to identify the main approaches that can create conditions for the formation of an interested attitude of senior citizens to systematic physical education (PE) classes and motivation for active longevity. In order to determine the level of physical functioning, a battery of tests was used, including an assessment of walking speed, balance and a test with rising from a chair (The short physical performance battery, SPPB). To determine the level of quality of life, the SF-36 Health Status Survey quality of life assessment questionnaire was used. Results and conclusions. The conducted testing allows us to state that PE classes significantly improve the physical functioning of older people and increase their quality of life. In particular, subjects involved in physical culture demonstrated higher rates of walking speed, balance, and lower limb strength. They do not have signs of frailty syndrome, unlike those not involved in physical culture. The results of the survey using the SF-36 Health Status Survey questionnaire showed that those involved in physical culture perform everyday activities (walking, climbing stairs, etc.) more easily, and their subjective health assessment is higher than that of those not involved in physical culture. Therefore, conditions should be created to develop interest in physical culture, health-preserving behavior, and motivation for active longevity in elderly people by means of adaptive physical culture, taking into account age restrictions on health in the contingent. Particular attention should be paid to the development of motivation for active longevity in the age groups of 65-69 years and 70-74 years, where the maximum spread of physical functioning indicators and quality of life (general physical component) was recorded.